2021
DOI: 10.3390/s21072298
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Fruity Aroma Intensity and Defect Presence in Virgin Olive Oil Using an Electronic Nose

Abstract: The organoleptic profile of a Virgin Olive Oil is a key quality parameter that is currently obtained by human sensory panels. The development of an instrumental technique capable of providing information about this profile quickly and online is of great interest. This work employed a general purpose e-nose, in lab conditions, to predict the level of fruity aroma and the presence of defects in Virgin Olive Oils. The raw data provided by the e-nose were used to extract a set of features that fed a regressor to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 45 publications
(40 reference statements)
1
12
0
Order By: Relevance
“…To reduce the influence of ambient temperature and humidity, the signal was denoised and smoothed, and E-nose data were divided into calibration sets and prediction sets after removing outliers. The maximum response value [41] was selected as the extraction feature representing the processed signal for subsequent analysis. Principal component analysis (PCA), partial least squares discriminant analysis (PLS-DA), linear discriminant analysis (LDA), and classification and regression trees (CART) were used to establish early discrimination models of C. fimbriata-infected sweetpotatoes during the asymptomatic period.…”
Section: Discussionmentioning
confidence: 99%
“…To reduce the influence of ambient temperature and humidity, the signal was denoised and smoothed, and E-nose data were divided into calibration sets and prediction sets after removing outliers. The maximum response value [41] was selected as the extraction feature representing the processed signal for subsequent analysis. Principal component analysis (PCA), partial least squares discriminant analysis (PLS-DA), linear discriminant analysis (LDA), and classification and regression trees (CART) were used to establish early discrimination models of C. fimbriata-infected sweetpotatoes during the asymptomatic period.…”
Section: Discussionmentioning
confidence: 99%
“…Both lab-made and commercial apparatus have been used for oils' adulteration detection [20] to identify specific aroma markers in oils extracted from olives with anthracnose [21], for assessing oils' quality grade and oils' blends discrimination [22,23], or to establish aroma fingerprints of extra virgin olive oils (EVOO) [24]. More recently, Teixeira et al [25] and Cano Marchal et al [26] have used E-noses to classify VOOs according to their fruitiness intensity or to detect sensory defects. Nevertheless, it should be pointed out that the electrical signals of the gas sensors, comprised in an E-nose device, highly depend on the capacity of controlling the sampling/analysis conditions, namely, temperature, moisture, pressure, gas speed, and vapor phase concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the study demonstrated the capability of the E-nose in the monitoring of the evolution of oil flavor during storage. Marchal et al (2021) [133] utilized a commercial E-nose (10 MOS sensors) to predict the intensity of the fruity attribute and off-flavors in VOOs, proposing to apply it for a fast screening of VOO quality.…”
Section: Quality Indicator Methodsmentioning
confidence: 99%